Características del consumo de etanercept, infliximab y adalimumab en el servicio de reumatología y dermatología del hospital nacional edgardo rebagliati martins – essalud, 2008 – 2009” - Castillo Rojas, Gaby Roxana (2010)
This thesis is a descriptive, cross-sectional and retrospective, whose overall objective is to determine the use of Infliximab, Etanercept and Adalimumab in the Department of Rheumatology and Dermatology, Hospital Nacional Edgardo Rebagliati Martins - EsSALUD, 2008-2009. The sample universe consisted of the computerized registry of consumption and cost, monthly obtained from the database Hospital Management System - Pharmacy unit dose (FUS), in the period from January 1, 2008 to December 31, 2009. Were employed Defined Daily Dose (DDD) to determine the consumption of Infliximab, Etanercept and Adalimumab in the hospital and outpatient, as appropriate, in the National Hospital Edgardo Rebagliati Martins 9.25 DDD/100 bed-days to Infliximab, 0.55 DDD/1000 attention-day Etanercept and 0.21 DDD/1000 attention-day Adalimumab in annual average. The total annual cost of Infliximab, Etanercept and Adalimumab for the National Hospital Edgardo Rebagliati Martins was S/.1572723.991; S /. 1442219.26 and S /. 591333.80 respectively